Melatonin Inhibits NF-κB/CREB/Runx2 Signaling and Alleviates Aortic Valve Calcification - Li, Shao-Jung; Cheng, Wan-Li; Kao, Yu-Hsun; Chung, Cheng-Chih; Trang, Nguyen Ngoc; Chen, Yi-Jen (Frontiers in Cardiovascular Medicine, 2022)
Calcific aortic valve disease (CAVD) is linked to high mortality. Melatonin inhibits nuclear factor-kappa B (NF-κB)/cyclic AMP response element-binding protein (CREB), contributing to CAVD progression. This study determined the role of melatonin/MT1/MT2 signaling in valvular interstitial cell (VIC) calcification. Western blotting and Alizarin red staining were used to analyze NF-κB/CREB/runt-related transcription factor 2 (Runx2) signaling in porcine VICs treated with an osteogenic (OST) medium without (control) or with melatonin for five days. Chromatin immunoprecipitation (ChIP) assay was used to analyze NF-κB's transcription regulation of NF-κB on the Runx2 promoter. OST medium-treated VICs exhibited a greater expression of NF-κB, CREB, and Runx2 than control VICs. Melatonin treatment downregulated the effects of the OST medium and reduced VIC calcification. The MT1/MT2 antagonist (Luzindole) and MT1 receptor neutralized antibody blocked the anticalcification effect of melatonin, but an MT2-specific inhibitor (4-P-PDOT) did not. Besides, the NF-κB inhibitor (SC75741) reduced OST medium-induced VIC calcification to a similar extent to melatonin at 10 nmol/L. The ChIP assay demonstrated that melatonin attenuated OST media increased NF-κB binding activity to the promoter region of Runx2. Activation of the melatonin/MT1-axis significantly reduced VIC calcification by targeting the NF-κB/CREB/Runx2 pathway. Targeting melatonin/MT1 signaling may be a potential therapeutic strategy for CAVD.